Boosting photoelectrochemical activities of heterostructured photoanodes through interfacial modulation of oxygen vacancies. (May 2017) - An, Xiaoqiang; Zhang, Le; Wen, Bo; Gu, Zhenao; Liu, Li-Min; Qu, Jiuhui; Liu, Huijuan
Abstract: Oxygen deficiency control has become an on-looming strategy for improving the catalytic ability of semiconductors, while the impact of defect distribution on the separation of charge carriers is still an open question. Herein, TiO2 /Bi2 WO6 heterostructures are used as a typical model to demonstrate the hypothesis of boosting photoactivity of photoanodes through modulating the spatial distribution of oxygen vacancies. Compared to pristine TiO2, significantly improved photoelectrochemical performance is achieved through suppressing intrinsic defects in Bi2 WO6 and tuning the formation sites of interfacial oxygen vacancies. Both experimental and theoretical investigations demonstrate that the distribution of interfacial oxygen vacancies around interface of Bi2 WO6 and in the TiO2 side is beneficial for the efficient extraction of photogenerated electrons toward counter electrodes. This research shed atomic-level insight into the interfacial modulation of defect distribution. Therefore, it provides a new principle to develop efficient heterostructures for photoelectrochemical and photocatalytic applications. Graphical abstract: Highlights: The spatial distribution of oxygen vacancies in heterostructured photoanodes were investigated. Significantly enhanced photoelectrochemical performance is achieved by defect modulation. Photoactivity of Bi2 WO6 was boosted by suppressing intrinsic oxygen vacancies in W-O-W layers. Oxygen vacancies around interface of Bi2 WO6 and in TiO2 side is beneficial for charge separation.